2011
DOI: 10.1117/1.3652709
|View full text |Cite
|
Sign up to set email alerts
|

Retinal image restoration by means of blind deconvolution

Abstract: Retinal imaging plays a key role in the diagnosis and management of ophthalmologic disorders, such as diabetic retinopathy, glaucoma, and age-related macular degeneration. Because of the acquisition process, retinal images often suffer from blurring and uneven illumination. This problem may seriously affect disease diagnosis and progression assessment. Here we present a method for color retinal image restoration by means of multichannel blind deconvolution. The method is applied to a pair of retinal images acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…Manual focusing is error prone, especially when performed by inexperienced photographers, and may lead to images that require additional restoration or enhancement. 3 The auto-focus feature offered in new retinal cameras is a significant advance that ultimately leads to a more robust imaging system, especially for medical screening purposes. On the other hand, the auto-focus feature still relies on the split-line mechanism, whereas in this work we propose a passive focus measure (FM) completely based on image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Manual focusing is error prone, especially when performed by inexperienced photographers, and may lead to images that require additional restoration or enhancement. 3 The auto-focus feature offered in new retinal cameras is a significant advance that ultimately leads to a more robust imaging system, especially for medical screening purposes. On the other hand, the auto-focus feature still relies on the split-line mechanism, whereas in this work we propose a passive focus measure (FM) completely based on image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This paper follows Ref. 4 but addresses a more general problem: restoration of retinal images in the presence of an SV PSF. In Ref.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…In Ref. 4, we showed that the single image blind deconvolution for blurred retinal images does not provide a suitable restoration. Moreover, in images with SV blur, the restoration is even worse.…”
Section: Description Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations